Towards Jewish-Arab normalization in Israel: Israeli Arabs want a more pragmatic politics while Jewish parties court the Arab vote - Lidia Averbukh (Stiftung Wissenschaft und Politik (SWP), 2021)
In the run-up to the 2021 elections to the Knesset, Jewish parties are actively courting the votes of Israeli Arabs, who constitute 17 per cent of all Israelis eligible to vote. At the same time, Israeli Arabs are increasingly emphasizing the need for a politics that will help improve their living circumstances and allow them greater political participation. While the Joint List alliance of Arab parties continues to follow its traditional oppositionist course and has come to terms with the decision of one of its members, the Islamic Movement (Ra'am), to split away, the election campaign has seen the emergence of new Arab politics, whose actors advocate a more pragmatic approach and are looking to cooperate with Jewish parties. The Israeli-Palestinian conflict and the identity of the Jewish state of Israel are playing a secondary role. The situation is similar in Israeli local politics, where Jews and Arabs are already engaged in interest-based cooperation.
Keywords: 320